Decreased Ovarian Reserves With an Increasing Number of Previous Early Miscarriages: A Retrospective Analysis - Tan, Jifan; Luo, Lu; Jiang, Jiaxin; Yan, Niwei; Wang, Qiong (Frontiers in Endocrinology, 2022)
The fact of ovarian reserve (OR) decreased in women with recurrent miscarriage has been well known. However, Whether OR would decrease with increasing numbers of previous miscarriages (PMs) is still unclear. To address this, OR parameters of following four groups’ patients were evaluated: 99 women with one previous miscarriage (PM1), 46 women with two previous miscarriages (PM2) and 35 women with three or more previous miscarriages (PM3). The control group included 213 women without a history of miscarriage (PM0). The correlation of OR parameters and the proportion of diminished ovarian reserve (DOR) patients between the four groups were analyzed using Kendall’s Tau-B coefficients. The results showed the median anti-Müllerian hormone (AMH) levels were 4.04, 3.40, 3.14 and 2.55 respectively in the PM0, PM1, PM2 and PM3 groups, respectively (H=15.99, P = 0.001); the median antral follicle counts (AFCs) were 10, 8, 8 and 6, respectively (H=24.53, P < 0.001); and the proportions of DOR patients were 10.8%, 15.2%, 23.9% and 31.4% (χ2= 13.01, P = 0.005). In addition, AMH level and AFC correlated negatively with the number of PMs (correlation coefficients -0.154, P < 0.001; -0.205, P < 0.001 respectively), the proportion of DOR patients correlated positively with the number of PMs (correlation coefficients 0.156, P = 0.001). After stratification by age, AMH and AFC levels were still significantly lower in the PM3 group than the PM0 group (P < 0.05). The proportion of DOR patients between the PM0 and PM3 groups was statistically significant (P < 0.001). This study showed that AMH levels and AFCs decreased as well as the proportion of DOR patients increased significantly as the number of PMs increased. In conclusion, our study indicates decreased AMH levels and AFCs might be one of the factors contributing to early miscarriage.